Existentialism from Dostoevsky to Sartre (Meridian books ;, 1956)
Existentialism is perhaps the most misunderstood of modern philosophic positions-- misunderstood by reason of its broad popularity and general unfamiliarity with its origins, representatives, and principles. Existential thinking did not originate with Jean-Paul Sartre. It has prior religious, literary, and philosophic origins. In its narrowest formulation, it is a metaphysical doctrine, arguing as it does that any definition of man's essence must follow, not precede, an estimation of his existence. In Heidegger, it affords a view of Being in its totality; in Kierkegaard, an approach to that inwardness indispensable to authentic religious experience; for Dostoevsky, Kafka, and Rilke the existential situation bears the stamp of modern man's alienation, uprootedness, and absurdity; to Sartre it has vast ethical and political implications. This book contains only complete selections or entire works by the major thinkers.--From publisher description.